2023
DOI: 10.3390/cancers15123163
|View full text |Cite
|
Sign up to set email alerts
|

In Utero Exposure to Hormonal Contraception and Mortality in Offspring with and without Cancer: A Nationwide Cohort Study

Abstract: Approximately 400 million women of reproductive age use hormonal contraceptives worldwide. Eventually, pregnancy sometimes occurs due to irregular use. Use in early pregnancy is found to be associated with child morbidities including cancer, the main reason for disease-related death in children. Here, we add the missing piece about in utero exposure to hormonal contraception and mortality in offspring, including assessments of prognosis in children with cancer. In utero exposure to hormonal contraception may b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 45 publications
(64 reference statements)
0
1
0
Order By: Relevance
“…Other studies have reported positive relationships between progestin-only contraceptive use in the year prior to pregnancy and increased offspring wheezing at age 6 to 8 months ( 37 ), as well as increased childhood attention-deficit/hyperactivity disorder (ADHD) incidence (highest with greatest recency to time of conception and for progestin products, specifically) ( 38 ). An increased risk for specific cancers (eg, nonlymphoid leukemia) ( 39 ) has also been observed, along with research suggesting poorer prognosis associated with these cancers and higher mortality risk ( 40 ). Many of these outcomes have been demonstrated only in single cohorts, often with other studies reporting negative outcomes; thus, these preliminary developmental effects should be interpreted with caution (though they warrant further research).…”
mentioning
confidence: 98%
“…Other studies have reported positive relationships between progestin-only contraceptive use in the year prior to pregnancy and increased offspring wheezing at age 6 to 8 months ( 37 ), as well as increased childhood attention-deficit/hyperactivity disorder (ADHD) incidence (highest with greatest recency to time of conception and for progestin products, specifically) ( 38 ). An increased risk for specific cancers (eg, nonlymphoid leukemia) ( 39 ) has also been observed, along with research suggesting poorer prognosis associated with these cancers and higher mortality risk ( 40 ). Many of these outcomes have been demonstrated only in single cohorts, often with other studies reporting negative outcomes; thus, these preliminary developmental effects should be interpreted with caution (though they warrant further research).…”
mentioning
confidence: 98%